Macheso’s Sungura and Social Identity Narratives in Postcolonial Zimbabwe - Chamisa, Vimbai (Palgrave Macmillan, 2022)
The focus of this article is on Sungura, a Zimbabwean Popular music style that has emerged and gained massive popularity after independence in Zimbabwe. Against the backdrop of Social identity theory, its aim is to interrogate the evident interest in Sungura music for both its performers and audiences in order to ascertain how it is an expression of the lives and identities that have emerged through certain socio-political and economic circumstances in Zimbabwe. To achieve this, the study focuses on the historical background of Alick Macheso’s music examining how his life history has influenced the nature of his Sungura. I later turn to selected songs by the musician to understand how the songs enable the expression of collective identities in Postcolonial Zimbabwe. I suggest that Macheso’s life history has influenced his music, shaping and defining it with a unique social meaning. This history articulates discourses of Social identity as it parallels the nature of the production of power within everyday human interactions typical in Postcolonial Zimbabwe.